The optimization of calcareous soil cation exchange capacity via the feather hydrolysate and N-P fertilizers integration - Doaa A. Goda; Eman H. El-Gamal; Mohamed Rashad; Yasser R. Abdel-Fattah (Scientific Reports)
Abstract Adding organic amendments to agricultural systems as sustainable practices is one of the most important stages toward creating a more sustainable and environmentally friendly food system. By increasing soil fertility and nutritional content, organic fertilizers increase plant productivity. Cation Exchange Capacity (CEC) is a vital indicator of soil fertility and plant nutrient availability, which is considered one of the most significant chemical parameters that affect agricultural soil quality. The main goals of the present study were to generate protein lysate from discarded feathers (enriched in different amino acids) through solid-state fermentation using Box-Behnken design (BBD). Then, assess the efficacy of hydrolyzed feather product (as an organic amendment), time, and N-P fertilizers on soil-CEC planted with maize in calcareous soil utilizing an optimization strategy that employed the central composite design and the response surface methodology (RSM). The results revealed that the protein concentration in the customized conditions was 1173.53 µg ml−1. With a predicted CEC of 31.416 cmolc kg−1, the ideal circumstances for the three variables under investigation of feather hydrolysate, time, and chemical fertilizer were 20.147 ml kg−1 soil, 27 days, and 42.3% of the recommended dose, respectively. Using keratin hydrolysate (20 ml kg−1 soil) as a soil amendment significantly improved the growth parameters of maize. The leaf surface area (SA, m2 gm−1) was increased by 695% and 37% compared to the control (without any addition) and N-P fertilizer treatments (100% of the recommended dose), respectively. Keratin hydrolysate as a sustainable production of value-added organic fertilizer applied to calcareous soil shows a synergistic effect on soil-CEC and plant growth parameters.